Effect of sludge age on methanogenic and glycogen accumulating organisms in an aerobic granular sludge process fed with methanol and acetate. Issue 5 (8th June 2015) - Pronk, M.; Abbas, B.; Kleerebezem, R.; van Loosdrecht, M. C. M.
Summary The influence of sludge age on granular sludge formation and microbial population dynamics in a methanol‐ and acetate‐fed aerobic granular sludge system operated at 35°C was investigated. During anaerobic feeding of the reactor, methanol was initially converted to methane by methylotrophic methanogens. These methanogens were able to withstand the relatively long aeration periods. Lowering the anaerobic solid retention time (SRT) from 17 to 8 days enabled selective removal of the methanogens and prevented unwanted methane formation. In absence of methanogens, methanol was converted aerobically, while granule formation remained stable. At high SRT values (51 days), γ‐Proteobacteria were responsible for acetate removal through anaerobic uptake and subsequent aerobic growth on storage polymers formed [so called metabolism of glycogen‐accumulating organisms (GAO)]. When lowering the SRT (24 days), Defluviicoccus‐related organisms (cluster II) belonging to the α‐Proteobacteria outcompeted acetate consuming γ‐Proteobacteria at 35°C. DNA from the Defluviicoccus‐related organisms in cluster II was not extracted by the standard DNA extraction method but with liquid nitrogen, which showed to be more effective. Remarkably, the two GAO types of organisms grew separately in two clearly different types of granules. This work further highlights the potential of aerobic granular sludge systems to effectively influence the microbial communities through sludge age control in order to optimize the wastewater treatment processes.